Документи про Українську Військову Організацію в Державному архіві Львівської області - Штокало, В. О. (Видавництво Національного університету "Львівська політехніка", 2009)
Дослідження продовжує аналіз збережених джерел про Українську Військову Організацію (УВО) як суб’єкта Національно-визвольного руху ХХ ст. Зокрема, розглядаються та зводяться в єдине ціле документи (зшиті в архівні справи), що були заведені на Українських землях (Львівське воєводство) окупаційним режимом (Друга Речпосполита Польська). This research continues the analysis of the preserved sources about Ukrainian Military Organization (UVO) as a subject of the National liberation motion in XX century. In particular, in the article the documents (sewn together in the archived folders), which were led on the Ukrainian lands (Lviv province) by occupation regime The Second Rechpospolita Polish are examined and settled in the entity. At the same time the discovered units, which was contained in the soviet “special departments”, are entered to the scientific circulation.